La peste justinienne en Égypte - Nicolas Morand (Les Nouvelles de l’Archéologie, 2022)
Between the 6th and 8th centuries AD, several episodes of bubonic plague struck the Mediterranean and European worlds. This pandemic is described in several ancient texts as the "Justinian plague". Research on these episodes has been developing significantly over the past few years with the discovery of cemeteries in link to the epidemic. DNA analyses carried out on human skeletons have made it possible to confirm the infection. They determine the genetic make-up of the bacterium (Yersinia pestis). But the research does not stop there, archaeozoology plays an important role in the knowledge about the spread of the plague. Indeed, black rats (Rattus rattus) are the main propagators of the plague through their infected fleas (Xenopsylla cheopis). Archaeological evidence of rats is therefore a means of tracing the spread of the animal. It is possible to cross-reference this data with textual sources and genetic studies. This article provides a synthesis of interdisciplinary research and the case of Egypt in the history of this zoonosis in the light of recent archaeozoological studies in Alexandria.